Superficial tension of pure metals - Jurov, V.M. (Publishing House of the KarSU named after E.A.Buketov, 2011)
In work questions of experimental definition of a superficial tension of massive samples and nanoparticles pure metals are considered. The model allowing with good accuracy to define size of a superficial tension, its dependence on temperature and on the size of particles is offered. Results of calculations are compared to known models and a method of "zero creep». Work is executed within the limits of the Program of basic researches of Ministry of Education and Science of the Republic of Kazakhstan. The grant 1034 FI.
Keywords: superficial tension; massive samples; nanoparticles; magnetic susceptibility; nanocrystals